Subhāshanāṃ senānīo : Śāhanavāza, Sahagāla, ane Ḍhīloṃnā jīvananī preraka parākrama kathā - Varmā, Nirañjana, 1917-1951 (SAMP early 20th-century Indian books project, 1946)
Brief biographies of Major General Śāhanavāza Khām̐, Col. Premakumāra Sahagala, and Col. Gurubkshasiṃha Ḍhīloṃ, officers in the Indian National Army formed by Subhash Chandra Bose during the Indian freedom movement and World War, 1939-1945.